Airborne radar survey above Vostok region, east-central Antarctica: ice thickness and Lake Vostok geometry - I. Tabacco; A. Forieri; C. Bianchi; A. Zirizzotti; E. Zuccheretti; A. Della Vedova (Journal of Glaciology, 2002)
During the 1999-2000 Italian Expedition, an airborne radar survey was performed along 12 transects across Lake Vostok, Antarctica, and its western and eastern margins. Ice thickness, subglacial elevation and the precise location of lake boundaries were determined. Radar data confirm the geometry derived from previous surveys, but with some slight differences. We measured a length of up to 260 km, a maximum width of 81 km and an area of roughly 14 000 km 2. Along the major axis, from north to south, the ice thickness varies from 3800 to 4250 m, with a decreasing gradient. From west to east the ice thickness is fairly constant, except for two narrow strips located on the western and eastern margins, where it increases with high thickening rate. Over the lake the surface elevation increases from 3476 m a.s.l. (south) to 3525 (north), with a decreasing gradient, while the lake surface elevation decreases from -315 to -750 m a.s.l., with a decreasing gradient (absolute value). The ice-surface and lake-ceiling slopes suggest that the lake is in a state of hydrostatic equilibrium.